Prevalence of Metabolic Syndrome Among Patients with Type 2 Diabetes at the Bon Samaritain University Hospital Complex in N’Djamena, Chad - Suitambaye Noubaramadji Yamti; Abel Dafogo Djibagaou; Koutaya Dezoumbe; Amine Akouya; Zita Aleyo Nodjikouambaye; Andrillene Laure Deutou Wondeu; Brahim Boy Otchom; Sabrina Atturo; Giulia Cappelli; Vittorio Colizzi (Universitas Ahmad Dahlan, 2025)
Introduction: The Metabolic Syndrome (MS) is characterized by the presence of at least three of the following five factors: abdominal obesity, hypertriglyceridemia, low HDL-cholesterol, glucose intolerance or type 2 diabetes, hypertension. It is relatively common with a prevalence that increases with age and predisposes to the occurrence of cardiovascular complications, hence the motivation of this study, the aim of which was to determine its prevalence in a Chadian population. Method: We conducted a prospective study involving 115 subjects aged 20 to 80 received at the Biochemistry laboratory as part of a monthly visit. The anthropometric and clinical data were recorded, and the biochemical parameters were analyzed on the PENTRA C400 automaton. The MS was defined according to the criteria of the NCEP-ATP III (2001). All of these data were analyzed using Excel 2013 and IBM SPSS software. Results: in our study the prevalence of MS is 72.2% of cases with a female predominance of 86.15% and it increases with age. The most frequent components of the metabolic syndrome were abdominal obesity (71%), arterial hypertension (45%), hypo HDL-cholesterol. Conclusion: our results show a high prevalence of MS and its main components which are abdominal obesity, arterial hypertension, hypo HDL-cholesterol, explaining in parallel a high level of cardiovascular risk. Management should be multidisciplinary to optimize the risk of chronic complications.